Comparison of drinking prevalence among Thai youth before and after implementation of the Alcoholic Beverage Control Act. (3rd May 2020) - Assanangkornchai, Sawitri; Saingam, Darika; Jitpiboon, Walailuk; Geater, Alan F.
ABSTRACT: Background: Underage drinking contributes to numerous health and social problems among adolescents. The Alcoholic Beverage Control Act, issued in Thailand in 2008, contains several clauses aiming at preventing underage and novice drinking, such as raising the minimum legal purchasing age from 18 to 20, banning alcohol sale and consumption in places frequented by youth, and banning alcohol advertisements. Objectives: To estimate the changes in the prevalence of alcohol consumption and perceptions of drinking norms among high-school students 8 years after the Act was implemented. Methods: Data from the Thai national high-school surveys in 2007 (N = 50, 033; 49.9% female) and 2016 (N = 38, 535; 49.8% female), using similar questionnaires, were analyzed. Prevalence rates and group norms toward drinking were compared between the two surveys, using weighted Poisson regression and prevalence ratios. Results: Drinking prevalence significantly increased in females, with prevalence ratios ranging from 1.2 for 30-day intoxication to 2.1 for 30-day binging. In males, the 12-month drinking prevalence increased in 2016, but a non-significant change for binge drinking and a 40% decrease for intoxication was seen. Higher proportions of students in 2016 perceived that most of their friends also drank alcohol compared to students in 2007 (16.8% vs. 11.2%; 49.8% increase). A significant effect of the year of survey on drinking patterns was seen across all school levels. Conclusion: Drinking rates decreased among males, but increased in females. These changes may be somewhat due to the Act, or to changes in the social environment in Thailand over this 8-year period.